2016
DOI: 10.19082/2395
|View full text |Cite
|
Sign up to set email alerts
|

Competence of nurses in the intensive cardiac care unit

Abstract: IntroductionCompetence of nurses is a complex combination of knowledge, function, skills, attitudes, and values. Delivering care for patients in the Intensive Cardiac Care Unit (ICCU) requires nurses’ competences. This study aimed to explain nurses’ competence in the ICCU.MethodsThis was a qualitative study in which purposive sampling with maximum variation was used. Data were collected through semi-structured interviews with 23 participants during 2012–2013. Interviews were recorded, transcribed verbatim, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 45 publications
(59 reference statements)
2
16
0
3
Order By: Relevance
“…As well as, Chaboyer, Chamberlain, Hewson-Conroyetal (2013) clarified that it is important that the relationship between safety culture and basic competence is examined together and attended to in intensive care units and that the nurses" competence is related to quality of nursing care in ICUs and this was in the same line with our study result. Moreover, our study result was supported by the study of Nobahar (2016) which showed that having competence leads to an improved quality of patient care and an increased patient satisfaction with the nurses and helps to promote nursing as a profession and improve nursing education and clinical nursing.…”
Section: Discussionsupporting
confidence: 60%
“…As well as, Chaboyer, Chamberlain, Hewson-Conroyetal (2013) clarified that it is important that the relationship between safety culture and basic competence is examined together and attended to in intensive care units and that the nurses" competence is related to quality of nursing care in ICUs and this was in the same line with our study result. Moreover, our study result was supported by the study of Nobahar (2016) which showed that having competence leads to an improved quality of patient care and an increased patient satisfaction with the nurses and helps to promote nursing as a profession and improve nursing education and clinical nursing.…”
Section: Discussionsupporting
confidence: 60%
“…A critical care unit is a unit where patients with critical conditions are admitted, so nurses working in these units are required to have clinical competences [7,8]. On the other hand, critical care units must have certain standards.…”
Section: Introductionmentioning
confidence: 99%
“…World Health Organization (WHO) requires all the member countries to report and implement their plans for strengthening nurses and equipping them with professional competency [ 8 ]. Having competency leads to an improved quality of patient care and an increased patient satisfaction with the nurses and helps promote nursing as a profession and improve nursing education and clinical nursing [ 9 ]. In addition, patients expect nurses to be competent and to behave them in a reasonable way.…”
Section: Introductionmentioning
confidence: 99%